Condições sociodemográficas e de saúde de pessoas idosas hospitalizadas por fratura de fêmur - Perosa, Joice (2023)
Fractures are among the main health problems resulting from falls among elderly people, with femur fractures being one of the most frequent and leading to worse outcomes, including death. Expenses for treatment and rehabilitation are high and draw attention to a different look at this condition in relation to public health policies. The study aims to outline an epidemiological and clinical profile of elderly people hospitalized with a femur fracture in a teaching hospital in the interior of the state of Rio Grande do Sul, identifying the reasons for the fall, previous health conditions, such as comorbidities, occurrence of polypharmacy and functionality, incidence of clinical intercurrences in the perioperative period and, finally, demonstrate the time between the fracture and the surgical procedure, its implications and outcomes. This is an observational, descriptive, and cross-sectional study, with 74 elderly people hospitalized with hip fractures for the orthopedics team at a teaching hospital, between the second half of December 2021 and the end of May 2022. questionnaire consisting of profile data, life habits, anthropometric data, history of fractures and falls, reason for the fall, use of mobility aids and type of fracture. The questionnaire also sought to identify comorbidities defined as conditions pre-existing to the fracture and medications for continuous use, assessing the occurrence of polypharmacy. The waiting time between the fracture and hospitalization with the orthopedic team and the time elapsed from this until the surgical procedure for correction were indicated, as well as the total hospitalization time. For data analysis, they were tabulated in a Microsoft Excel spreadsheet and statistical analysis was conducted using SPSS Statistics version 26. The findings recorded, in line with other Brazilian and international studies, a higher incidence in females, the progressive increase in cases with increasing age, the vulnerable profile of the studied population, the high incidence of comorbidities and perioperative clinical intercurrences. One of the main reasons for clinical decompensation is waiting for hospitalization with an orthopedic team and, therefore, delay in surgical correction of the fracture.